(untitled) (Conference on English Language Teaching, 2025)
This study examines public judgment of Indonesia’s proposed selective 12% VAT increase on luxury goods, announced by President Prabowo Subianto, through an appraisal analysis of YouTube comments. Employing a qualitative approach that integrates Critical Discourse Analysis (CDA) with Appraisal Theory, the research focuses on the Judgment subsystem—specifically Social Esteem (ability, persistence, normality) and Social Sanction (honesty and ethical conduct)—to explore how netizens evaluate government policy. By analyzing these online reactions, the study reveals the moral and evaluative dimensions that shape public perceptions of fiscal decisions. Findings indicate that language in political discourse functions as a key tool for expressing social and ethical judgments. The comments reflect polarized attitudes toward the policy, demonstrating steadfastness in both support and opposition. The critiques frequently question the government’s capacity to implement effective reforms and challenge deviations from perceived social norms. Additionally, propriety judgments dominate discussions on the fairness of taxing the middle class while allegedly favoring the wealthy. This analysis highlights that public responses to political decisions are embedded in moral evaluations of truthfulness, competence, fairness, and ethical conduct. Negative judgments arise primarily from perceived mismatches between government actions and public expectations.